Shock Management and Hemodynamic Monitoring of Severe Dengue with Fluid Overload: A Case Report - Asbi, Shinta; Indra Ihsan; Rinang Mariko (HM Publisher, 2024)
Background: Dengue shock syndrome (DSS) is a life-threatening complication of dengue infection characterized by plasma leakage, shock, and organ dysfunction. Fluid management is crucial in DSS, but fluid overload can lead to adverse outcomes. This case report highlights the challenges and strategies in managing DSS with fluid overload. Case presentation: An 8-year-old girl presented with severe dengue, DSS, encephalopathy, and fluid overload. She had a history of high fever, vomiting, and altered consciousness. Initial management focused on fluid resuscitation, but the patient developed signs of fluid overload. Hemodynamic monitoring using USCOM (Ultrasonic Cardiac Output Monitor) revealed low cardiac output and high systemic vascular resistance. Fluid restriction and inotropic support with epinephrine were initiated. The patient's condition gradually improved, and she was discharged after complete recovery. Conclusion: This case emphasizes the importance of early recognition and careful monitoring of fluid status in DSS. Hemodynamic monitoring tools like USCOM can aid in guiding fluid management and identifying complications like fluid overload. Prompt intervention with fluid restriction and inotropic support can improve outcomes in DSS patients with fluid overload.